2015
DOI: 10.1093/tropej/fmv072
|View full text |Cite
|
Sign up to set email alerts
|

Animal Bites and Rabies Prophylaxis in Rural Children: Indian Perspective

Abstract: A prospective observational study was conducted in a tertiary care hospital to study clinicoepidemiological profile of potentially rabid animal bite cases from rural India. Total of 308 children (median age 6 years) admitted to hospital, were recruited over 1 year and followed up till completion of antirabies vaccine course. Dog was the commonest (77.27%) offending animal. Of the exposures, 66.88% were scratches, 88.96% were unprovoked and 27.27% were categorized as Class III. The median times to wound toileti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 11 publications
4
16
0
17
Order By: Relevance
“…Samanta et al have reported that the face and truncus are more in contact in young children (especially under the age of five) and right lower leg and left lower leg are the commonly affected regions in older children. The authors have also indicated that older children tend to agitate animals and have more bite marks on their extremities in order to defend themselves (12). Since cat contact was found more commonly in our study, hands and upper extremity were detected as frequent contact regions.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Samanta et al have reported that the face and truncus are more in contact in young children (especially under the age of five) and right lower leg and left lower leg are the commonly affected regions in older children. The authors have also indicated that older children tend to agitate animals and have more bite marks on their extremities in order to defend themselves (12). Since cat contact was found more commonly in our study, hands and upper extremity were detected as frequent contact regions.…”
Section: Discussionsupporting
confidence: 57%
“…In a study by Samanta et al reviewing 308 pediatric patients with rabies suspected contact, male children were nearly twice in number compared to females and children over the age of 5 were detected most frequently among all. This difference was associated with the fact that boys were more interested in outdoor activities compared to girls (12).…”
Section: Discussionmentioning
confidence: 99%
“…[8,13] One study reported children below 5 years had significantly greater incidence of bites on face and trunk than children more than 5 years of age. [15] This may be attributed to their playful nature, running at sight of dogs and short stature. Majority of the victims 84.7% had Category III.…”
Section: Discussionmentioning
confidence: 99%
“…Samanta ve arkadaşları küçük çocuklarda (özellikle beş altı çocuklar) büyük çocuklara göre daha fazla yüz ve gövdenin temas ettiğini, büyük çocuklarda ise sağ alt bacağın ve ardından sol alt bacağın en sık etkilenen bölgeler olduğunu bildirmişlerdir. Yazarlar daha büyük çocukların hayvanları kızdırmak gibi kötü davranış eğilimlerinin olması ve köpek saldırılarına karşı kendilerini savunmaları gereği ekstremitelerde daha fazla ısırık olduğunu belirtmişlerdir (12). Çalışmamızda kedi ile temas daha fazla olduğu için el ve üst ekstremite daha sık temas bölgesi olarak bulunmuştur.…”
Section: Discussionunclassified